Economic Life of the Jews of Koya, 1918-1951 - Ahmed, Bzhar Othman (IIUM Journal of Religion and Civilisational Studies, 2026)
This study aims to analyse the economic conditions of Jews in the city of Koya (Iraqi Kurdistan) from 1918 to 1951. From the outset of Jewish migration from Palestine to Iraq and Kurdistan, the Jews swiftly blended into Kurdish society and embraced its lifestyle. This led to the Jewish population distinguishing themselves from others, especially in economic activities. Their economic conditions differed, particularly in Koya. This research is essential as no studies have been conducted on the economic contributions of the Jewish community in Koya, despite their vital role in the economic development of the Kurdish population. This study employs a qualitative historical and textual analysis method, utilising an exploratory qualitative research design based on primary and secondary sources. The findings show that Koya's Jewish community dominated profitable areas such as jewellery, textiles, tailoring, spirits, and fragrances, which were essential to the economy. Their distinctive features were audacity and proficiency in business and professional endeavours.